A brief review of influenza virus infection. Issue 8 (14th April 2021) - Javanian, Mostafa; Barary, Mohammad; Ghebrehewet, Sam; Koppolu, Veerendra; Vasigala, VeneelaKrishnaRekha; Ebrahimpour, Soheil
Abstract: Influenza is an acute viral respiratory infection that affects all age groups and is associated with high mortality during pandemics, epidemics, and sporadic outbreaks. Nearly 10% of the world's population is affected by influenza annually, with about half a million deaths each year. Influenza vaccination is the most effective method for preventing influenza infection and its complications. The influenza vaccine's efficacy varies each season based on the circulating influenza strains and vaccine uptake rates. Currently, three antiviral drugs targeting the influenza virus surface glycoprotein neuraminidase are available for treatment and prophylaxis of disease. Given the significant burden of influenza infection globally, this review is focused on the latest findings in the etiology, epidemiology, transmission, clinical manifestation, diagnosis, prevention, and treatment of influenza.